Measurement of transient electromagnetic coupling and interference caused by disconnector operation in substation. (January 2017) - Lihui, Wang; Jiayu, Huang; Jianfei, Ji; Fubin, Pang; Yubo, Yuan
Highlights: Transient transmission coupling model was established. The time-frequency domain characteristics were calculated. Electromagnetic disturbance test system in substation was designed. Abstract: Disconnector operation in the substation can cause transient electromagnetic disturbance and very fast transient over-voltage (VFTO), and will lead to the misoperation or damage of electrical protection system. To research the characteristics and influence of electromagnetic interference, principle of disconnector operation was analyzed. Then, an improved Agrawal model was adopted to describe the transmission line coupling process of disconnector operation, and telegraph equation was calculated by finite-difference time-domain (FDTD) method. With the model and method, the conduction process and characteristics of transient electromagnetic coupling and interference caused by disconnector operation in substation were simulated. Besides, disturbance voltage signal on the secondary cables caused by disconnector operation was measured in a 500 kV substation. Finally, parameters of transient electromagnetic coupling and interference in time domain and frequency domain were calculated respectively. Experiment results show that the quantitative level of transient electromagnetic coupling and interference caused by disconnector operation in substation can be evaluated in theory, and the core frequency points concerned in secondary circuit can be calculated.